Antibiotic-impregnated calcium sulfate for the treatment of pediatric hematogenous osteomyelitis - Rui Tao; Jian-qun Wu; Ji-wei Luo; Liang Hong; Chun-hao Zhou; Guo-yun Cheng; Cheng-he Qin (BMC, 2022)
Abstract Background Antibiotic-impregnated calcium sulfate has excellent curative efficacy in chronic osteomyelitis. However, its curative efficacy in pediatric hematogenous osteomyelitis has not been sufficiently studied. The purpose of this study was to evaluate the curative effects of antibiotic-impregnated calcium sulfate in the treatment of pediatric hematogenous osteomyelitis. Methods Overall, twenty-one pediatric patients with hematogenous osteomyelitis treated at our hospital between 2013 and 2018 were included for assessment. The clinical history, clinical manifestation, infection recurrence rate, sinus leakage, incision leakage, pathological fractures, bone growth and surgical procedures were analyzed. Results The infection recurrence rate was 0% (0/21) at a minimum of 31 months (range 31 to 91 months) of follow-up. Postoperative incision leakage was found in one pediatric patient. Osteolysis was found in one pediatric patient. Acceleration of bone growth occurred in one pediatric patient. Retardation of bone growth occurred in one pediatric patient. Genu valgus deformity occurred in one pediatric patient. Conclusions Although noninfectious complications occurred, the curative effect of antibiotic-impregnated calcium sulfate in pediatric hematogenous osteomyelitis was satisfactory.